Studies on the male genitalia of the phasmid : Phalces longiscaphum de Haan - Morsbach, W. O.(Wolfgang Oskar) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1957.